2017
DOI: 10.1163/15685381-00003107
|View full text |Cite
|
Sign up to set email alerts
|

Postautotomy tail movement differs between colour morphs of the red-backed salamander (Plethodon cinereus)

Abstract: Striped and unstriped colour morphs of the eastern red-backed salamander, Plethodon cinereus, vary in their preattack behavioural response to predators, but it is unknown whether the morphs vary in post-attack strategies. Both morphs employ tail autotomy, a post-attack defensive mechanism enabling an individual to release a portion of their tail to facilitate escape from predation. Postautotomy tail movement diverts attention of a predator away from the individual's body, so natural selection should favor vigo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Second, our study focused on how abiotic factors could maintain color polymorphism, but there may be additional biotic selection pressures that favor striped individuals at cool sites with low forest cover. For example, predation pressure may vary between striped and unstriped morphs due to differences in coloration (Lotter & Scott, ), behavior (Moreno, ; Venesky & Anthony, ; Otaibi, Johnson, & Cosentino, In press) or local frequency (i.e., frequency‐dependent selection; Fitzpatrick, Shook, & Izally, ). Striped and unstriped individuals also vary in diet (Anthony et al., ), territorial behavior (Reiter, Anthony, & Hickerson, ), and disease resistance (Venesky et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, our study focused on how abiotic factors could maintain color polymorphism, but there may be additional biotic selection pressures that favor striped individuals at cool sites with low forest cover. For example, predation pressure may vary between striped and unstriped morphs due to differences in coloration (Lotter & Scott, ), behavior (Moreno, ; Venesky & Anthony, ; Otaibi, Johnson, & Cosentino, In press) or local frequency (i.e., frequency‐dependent selection; Fitzpatrick, Shook, & Izally, ). Striped and unstriped individuals also vary in diet (Anthony et al., ), territorial behavior (Reiter, Anthony, & Hickerson, ), and disease resistance (Venesky et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Post‐autotomy appendage movement has evolved independently multiple times (Appendix S1) and is observed in lizards (Higham & Russell, ), salamanders (Labanick, ), and arachnids [harvestmen (Miller, ; Roth & Roth, ), spiders (Johnson & Jakob, ) and scorpions (Mattoni et al, ); of which some can regenerate and others cannot]. In some species, there is also inter‐population variation in the vigour of post‐autotomy appendage movement, which correlates with local predatory pressure (Cooper, Pérez‐Mellado, & Vitt, ; suggested in Cromie & Chapple, ; Otaibi, Johnson, & Cosentino, ). However, in other species, the duration of post‐autotomy body‐part movement is highly conserved (Pafilis, Valakos, & Foufopoulos, ; Pafilis, Pérez‐Mellado, & Valakos, ; Pafilis et al, ).…”
Section: Evolution Of the Autotomy Phenotypementioning
confidence: 99%
“…These differences in behavior and tail autotomy suggest that the two morphs experience different rates of predation, with the authors hypothesizing that unstriped morphs experience greater predation by T. sirtalis . After simulated predation (i.e., a tail clip), Otaibi, Johnson, & Cosentino (2017) found that the autotomized tails of striped morphs move longer and faster than those of unstriped morphs.…”
Section: (Ii) Differential Predation Risk By Colormentioning
confidence: 99%